Capacity Building in Participatory Monitoring and Evaluation on Sustainability of Food Security Irrigation Projects - O. Rogito (Journal of Engineering, Project, and Production Management, 2020)
Health-related problems and even death among animals and human beings. Agriculture is the main food source, thus, many interventions are made such as that of irrigation by the local county and national government initiated through the National Irrigation Board (NIB). Despite the irrigation projects food insufficiency still persists, therefore their sustainability is questionable. One such approach to improving the sustainability of irrigation projects is participatory monitoring and evaluation which leads to ownership and then higher sustainability. In the study, the objective was to asses if taking corrective action after participatory monitoring and evaluation (PME) influence project sustainability. The study used a descriptive survey and correlation designs to collect data from 316 respondents selected using stratification sand purposeful with strict randomization. Questionnaires were administered and interviews were conducted on selected sample respondents on appointed dates. Data were analyzed using SPSS version 25.0 to get descriptive statistics, correlations coefficients were obtained to test association and degree of strength. Testing of the hypothesis was done using linear regression. The study findings were that a large number of respondents were between ages 31 to 40 years and most were female with their highest level of education being primary school. The influence of PME capacity building on the dependent variable and irrigation projects sustainability found that the farmers were not taken for exposure visits and project officers were not accountable for money use. Age, gender, and education level have very minimal influence on PME capacity building. PME capacity building had a weak positive influence of r = 0.290 and it explained only 8.4% of irrigation projects sustainability in Kitui County. The study recommends that to improve project capacity building: project revenue must be controlled on use, farmers must be taken for exposure visits to learn from successors, project officers should be accountable for funds use, and project guidelines should be improved to increase sustainability. Implementation of these recommendations will reduce the loss of Arid and Semi-Srid Lands (ASALs) and attain higher and longer sustainability in food projects, thus, reducing the recurrence rate of food shortage, improve and hasten the implementation of irrigation projects, show the need to involve primary stakeholders in project monitoring and appraisal for sustainability, better and efficient decisions by policymakers to increase chances of project's success.